(3JaSjQ GdbQBf GdcQjes - (3CHhGdMSjf YHjO Gddg Hf CMeO Hf YHjO Gddg GHf CHj GdQHjY GdbQTj GdCehj GdYKeGfj GdGTHjdj,J (B688 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje (B: (3PgH GdHUQjhf Edi Cf GdJbOjQ (B: (3EHJOGFi HSe Gddg , agh YfOge NHQG eHJOC eMPha s
(3BNQgG (B:s
(3BNQ GdehLhO efg (B: (3hde fbd Ef CeI eYWha Ydi (B" (3fG (B" (3dCfg dG jaUd Hjf MQa GdYWa hGdeYWha EdG HGdXQa ahLg GdcdGe Cf jbGd ajg (B: (3Efg efUhH HGVeGQ s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B191s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJaSjQ hYdhe GdbQBfs